Enhancing Elementary Students’ Mathematical Representation Skills Through Higher Order Thinking Skills (HOTS) Practice Questions - Nurma Izzati; Minhatul Maula; Silvana Nurul Auliya; Robi'atun Robi'atun; Dzakiyyah Rosyidah Safinatunnajah; Fithrotusholihah Fithrotusholihah (MASI Mandiri Edukasi, 2025)
This study aims to 1) evaluate students' mathematical representation skills before participating in HOTS practice questions, 2) evaluate students' mathematical representation skills after participating in HOTS practice questions, and 3) determine the improvement in students' mathematical representation skills through HOTS practice questions. This research uses a quantitative method with a one-group pretest-posttest design. The research population included 60 fifth-grade students from SD Negeri 1 Pelandakan, Cirebon, with a sample of 30 students selected using purposive sampling. The instrument used was a mathematical representation skills test. Data were analyzed using the N-Gain test and paired sample t-test to compare pretest and posttest results. The study results show that: 1) the average mathematical representation skills of students before participating in HOTS practice questions was 67.83, classified as weak category; 2) the average mathematical representation skills of students after participating in HOTS practice questions was 85.38, clasified as strong category; and 3) there was a significant improvement in students' mathematical representation skills, with an average N-Gain score of 0.5551 and p < 0.000. This improvement falls under the moderate category and is statistically significant. These findings suggest that HOTS-based practice questions effectively enhance mathematical understanding and should inform curriculum and instructional planning.